Recognition of Social Rule Violation in “Deficit Syndrome” Schizophrenia: A Study Using Economic Games - Claassen, Christian; Langdon, Robyn; Brüne, Martin (Frontiers in Psychiatry, 2020)
Aberrant social behaviour is a frequent clinical feature of schizophrenia, and seems related to the duration and chronicity of the disorder. However, there is a paucity of research into the relationship between social behaviour and social cognition in patients with severe chronic courses of schizophrenia. Accordingly, the present study sought to examine the appreciation of social rules and norms such as fairness and cooperation in schizophrenia patients who fulfilled the criteria for “deficit syndrome”. To this end, we utilised a so-called Ultimatum Game, and a Dictator Game, in which participants had the option to punish others’ unfair behaviour. In addition, “theory of mind”, the ability to appreciate others’ mental states, was also examined using the Mental State Attribution Task (MSAT). Symptom severity was determined using the Positive and Negative Syndrome Scale. While patients with deficit schizophrenia responded to varying levels of fairness in similar ways to controls, the patients accepted fewer fair offers and engaged less in third-party punishment. Impaired theory of mind in patients reduced the latter, but not the former, group difference to non-significance. No significant correlations emerged between symptom severity and task performance. Together, these findings suggest that the understanding of others’ minds partly contributes to the appreciation of social rules and norms in patients with severe chronic courses of schizophrenia.